MgI2 immobilized nitrogen and phosphorus co-doped hollow carbon cubes as a multifunctional host for high-performance lithium‑sulfur batteries - Sheng Liang; Cong Li; Zi-Hao Chen; Lei Hu; Xin Liang; Ling-Li Liu; Li-Li Wang; Ning-Ning Zhou; Bin Chen; Wen-Yu Gu; San-E Zhu (Chemical Engineering Journal, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Improved mitigation of reverse osmosis membrane biofouling via synergistic UV light-emitting diodes and chlorine disinfection - Yu-jia Gao; Rui-ning Wang; Shi-tong Yu; Ke-fan Cao; Xu-Cheng Cai; Yu Hong; Yun Wang; Wei E. Huang; Nozomu Ikuno; Nakata Koji; Hong-ying Hu; Yin-hu Wu (Desalination, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Nonnegligible migration of rubber-derived chemicals from road surface to adjacent greenbelt soil - Zhen-Yu Ge; Hai-Yan Zhang; Xue-E Li; Yue-Hong Liu; Li-Ni Wei; Xiang-Ning Liang; Yan-Feng Lv; Tuan-Tuan Wang; Sai Wang; Jian-Liang Zhao (Journal of Hazardous Materials, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

Effects of gully topographic vertical zone on the spatial heterogeneity of root-soil complex shear performance in the loess plateau - Yuying Cao; Zhengchao Zhou; Mingyu Chen; Jun'e Liu; Peipei Wang; Ning Wang; Bingbing Zhu; Fang Liu; Liyi Wu; Di Yu (CATENA, 2026)

Melatonin Improves Neuroprotection and Neuroplasticity in Middle-Aged Mice Following Permanent Focal Cerebral Ischemia - Liang-Yi Chen; Shih-Huang Tai; Sheng-Yang Huang; Chih-Chieh Tsao; Yu-Ning Chen; Hao-Hsiang Hsu; Ai-Hua Lee; E.-Jian Lee (Molecular Neurobiology, 2026)

Comparative Population Genomics of Relictual Caribbean Island Gossypium hirsutum - Weixuan Ning; Guanjing Hu; Daojun Yuan; Mark A. Arick; Chuan‐Yu Hsu; Zenaida V. Magbanua; Olga Pechanova; Daniel G. Peterson; Yating Dong; Joshua A. Udall; Corrinne E. Grover; Jonathan F. Wendel (Molecular Ecology, 2026)
Gossypium hirsutum is the world's most important source of cotton fibre, yet the diversity and population structure of its wild forms remain largely unexplored. The complex domestication history of G. hirsutum combined with reciprocal introgression with a second domesticated species, G. barbadense , has generated a wealth of morphological forms and feral derivatives of both species and their interspecies recombinants, which collectively are scattered across a large geographic range in arid regions of the Caribbean basin. Here we assessed genetic diversity within and among populations from two Caribbean islands, Puerto Rico ( n = 43, five sites) and Guadeloupe ( n = 25, one site), which contain putative wild or introgressed forms. Using whole‐genome resequencing data and a phylogenomic framework derived from a broader genomic survey, we parsed individuals into feral derivatives and truly wild forms. Feral cottons display uneven levels of genetic and morphological resemblance to domesticated cottons, with diverse patterns of genetic variation and heterozygosity. These patterns are inferred to reflect a complex history of interspecific and intraspecific gene flow that is spatially highly variable in its effects. Wild cottons in both Caribbean islands appear to be relatively inbred, especially the Guadeloupe samples. Our results highlight the dynamics of population demographics in relictual wild cottons that experienced profound genetic bottlenecks associated with repeated habitat destruction superimposed on a natural ecogeographical distribution comprising widely scattered populations. These results have implications for conservation and utilisation of wild diversity in G. hirsutum .

Melatonin Promotes B-Cell Maturation and Attenuates Post-Ischemic Immunodeficiency in a Murine Model of Transient Focal Cerebral Ischemia - Shih-Huang Tai; Hao-Hsiang Hsu; Sheng-Yang Huang; Yu-Ning Chen; Liang-Yi Chen; Ai-Hua Lee; Ai-Chiang Lee; E.-Jian Lee (Journal of Neuroimmune Pharmacology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Effective decontamination of DR-81 dye from aqueous solutions using eco-friendly graphene oxide nanoparticles - Eslam Salama; Ahmed E. Mansy; Zhen-Yu Tian; Safaa Mohamed; Ning Li; Fawei Lin; Mona Ossman (Environmental Science and Pollution Research, 2024)

Divergent changes in particulate and mineral-associated organic carbon under natural revegetation along a soil texture gradient in temperate grasslands of China - Peipei Wang; Zhengchao Zhou; Wenfei Yu; Fang Liu; Yuying Cao; Jun’e Liu; Ning Wang (Soil and Tillage Research, 2024)

Manganese cycling and transport in boreal estuaries impacted by acidic Mn-rich drainage - Changxun Yu; Stephanie Turner; Simo Huotari; Ning Chen; Andrey Shchukarev; Peter Österholm; Margarita Lopez-Fernandez; Eva Högfors-Rönnholm; Varvara Sachpazidou; Sathish Mayanna; K. Johan Hogmalm; Joonas J. Virtasalo; et al. (Geochimica et Cosmochimica Acta, 2024)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Knowledge of Cervical Cancer, Human Papilloma Virus (HPV) and HPV Vaccination Among Women in Northeast China - Yu-e Ning; Yao Liu; Xiao-yu Xu; Xin-yu Zhang; Ning Wang; Li-qiang Zheng (Journal of Cancer Education, 2020)
This study aimed to research the understanding and knowledge of cervical cancer, human papilloma virus (HPV), and HPV vaccination, and the acceptance of HPV vaccination, among a population of women in northeastern China. A cross-sectional survey was carried out by questionnaire to investigate knowledge of cervical cancer, HPV, and HPV vaccination. The 230 female participants were native residents of northeastern China, and their ages ranged between 18 and 65 years. Questionnaires were randomly acquired by the respondents from online and paper questionnaire distribution. The questionnaire included questions on three major aspects to record people’s perceptions of cervical cancer, HPV, and vaccines. Of the sample of 230 women surveyed, 80.9% had heard of cervical cancer, but understanding was only 15.7%; 38.3% knew about HPV; 20% knew about HPV vaccine; 39.6% agreed to receive HPV vaccination, and the remainder were mainly concerned about its safety and effectiveness. Data analysis showed that age, family income, and whether there was experience of screening all influenced knowledge of cervical cancer, but this was not statistically significant. The level of education had no obvious effect on the degree of knowledge about cervical cancer; however, with an improvement in education, women’s awareness of HPV vaccine improved significantly ( p < 0.05). Women who have received cervical cancer screening had significantly greater knowledge about cervical cancer and HPV than those with no screening ( p < 0.05). Women in northeastern China have little knowledge of cervical cancer, HPV, and HPV vaccine, lack disease knowledge, and hold a skeptical attitude about HPV vaccination. Medical institutions are the main channel providing information to these women.

Competition for electrons between pyridine and quinoline during their simultaneous biodegradation - Hua Xu; Weihua Sun; Ning Yan; Danni Li; Xueqi Wang; Tingting Yu; Yongming Zhang; Bruce E. Rittmann (Environmental Science and Pollution Research, 2017)

Antibacterial mechanism of high-mobility group nucleosomal-binding domain 2 on the Gram-negative bacteria Escherichia coli - Heng Li; Xiao-fei Shen; Xin-e Zhou; Yan-e Shi; Lu-xia Deng; Yi Ma; Xiao-ying Wang; Jing-yu Li; Ning Huang (Journal of Zhejiang University-SCIENCE B, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Near infrared radiation protects against oxygen-glucose deprivation-induced neurotoxicity by down-regulating neuronal nitric oxide synthase (nNOS) activity in vitro - Zhanyang Yu; Zhaoyu Li; Ning Liu; Yunneng Jizhang; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Near infrared radiation rescues mitochondrial dysfunction in cortical neurons after oxygen-glucose deprivation - Zhanyang Yu; Ning Liu; Jianhua Zhao; Yadan Li; Thomas J. McCarthy; Clark E. Tedford; Eng H. Lo; Xiaoying Wang (Metabolic Brain Disease, 2015)

Genetic analysis and fine mapping of the Ga1-S gene region conferring cross-incompatibility in maize - Hua Zhang; Xu Liu; Yu’e Zhang; Chuan Jiang; Dezhou Cui; Huaihua Liu; Detao Li; Liwen Wang; Tingting Chen; Lihua Ning; Xia Ma; Huabang Chen (Theoretical and Applied Genetics, 2012)